Optimalisasi Konsentrasi dan Kinerja Guru: Implementasi Teknik Mindfulness bagi Guru SD Imanuel Palu: Optimizing Teachers’ Focus and Performance: Implementing Mindfulness Techniques at Imanuel Palu Elementary School - Jane Mariem Monepa; David Pakaya; Muthia Aryuni; Mayabi Pratika; Meilisa Silviana Patodo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Optimal concentration is an essential cognitive function for elementary school teachers facing high demands on multitasking and workload. However, the data indicate that many teachers struggle to maintain focus, which impacts learning quality and psychological well-being. This community service aimed to improve teachers' concentration through mindfulness training at Imanuel Palu Elementary School in Central Sulawesi. The method used a one-group pretest-posttest design with 16 participants. The training included the delivery of material and direct practice of mindfulness techniques (breathing exercises and full awareness). Concentration was measured using the Grit Concentration Test before and after the training. Results showed an increase in mean scores from 6.25 (pretest) to 9.75 (posttest). The Wilcoxon Signed-Rank Test yielded Z = -3.541 and p < 0.001, indicating a statistically significant improvement in concentration. All participants experienced increased scores. Thus, brief mindfulness technique training is effective in enhancing teacher concentration. This activity is recommended for adoption as part of sustainable professional teacher development.